2020
DOI: 10.9744/kata.22.1.10-16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Slang Words Formation Found in the Lyrics of Drake’s Songs

Abstract: This research attempted to find out the word formation processes of slang words found in the lyrics of Drake’s songs. This research applied descriptive qualitative research design. The theory of the 18 word formation processes based on the synthesized theories from Yule (2010), Mattielo (2008), O’Grady, Aronoff, & Dobrovolsky (1997) were used as guidelines. This study found out that there were 190 slang words existing in the lyrics of the songs. They were respectively categorized into clipping (27%), coina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…therefore, the word tryna is formed and generally used in written English informally. This is in accordance with previous research by Puspitorini (2019), Putri and Zakrimal (2019), Tanamal et al (2020), and Budasi and Bhuwana (2020) where blending words in lyrics written by native speakers were also found in informal words such as tryna, gotta, wanna, and ain't.…”
Section: Datasupporting
confidence: 93%
See 3 more Smart Citations
“…therefore, the word tryna is formed and generally used in written English informally. This is in accordance with previous research by Puspitorini (2019), Putri and Zakrimal (2019), Tanamal et al (2020), and Budasi and Bhuwana (2020) where blending words in lyrics written by native speakers were also found in informal words such as tryna, gotta, wanna, and ain't.…”
Section: Datasupporting
confidence: 93%
“…The last process found in lyrics written by Asian songwriters is multiple-process which has 24 data and mostly clipping as the second process is often found. This process is rarely found in the previous research yet Budasi and Bhuwana (2020) found 41 data of multiple-process in the Lyrics of Drake's Songs. In inflection, the data have the functions as verb and adjective.…”
Section: Datamentioning
confidence: 73%
See 2 more Smart Citations
“…According to the study, clipping is the most dominantly used word formation process to create the slangs across all songs in order to achieve a rhyme and beat balance. Identical types of studies have also been carried out by Aisyah & Larasati (2021) with Avril Lavigne's "Head Above Water" song, Budasi & Bhuwana (2020) with Drake's songs, Tanamal et al (2020) with Travis Scott on Astroworld Album.…”
Section: Introductionmentioning
confidence: 99%